The DEVELOPMENT OF AN AUTOMATIC BRAKING SYSTEM FOR A 4-WHEEL DRIVE : Fabrication and evaluation of an automatic braking system using locally sourced materials (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2022)
Internal Combustion Engines have been advanced a lot such that its speed is becoming a major catastrophe. Advanced automatic braking system improves braking techniques in vehicles. It changes complete braking systems in an automotive and deals with the concept of Automatic Braking System giving the solution. This work is designed with ultrasonic transmitter, ultrasonic receiver, Arduino UNO R3 board with PIC microcontroller, DC gear motor, servomotor and mechanical braking arrangement. The Ultrasonic Sensor generates (0.020-20) KHZ frequency signal. It is transmitted through ultrasonic transmitter. The ultrasonic receiver is used to receive the reflected wave present in front of the vehicle, then the reflected waves is given to the ultrasonic wave generator unit in which the incoming wave is amplified and compared with reference signals to maintain a constant ratio and this signal is given to microcontroller and through which the working of DC gear motor and Servomotor may takes place, which results in application of brakes. The prototype has been prepared depicting the technology and tested as per the simulated conditions.
Keywords: Automatic, braking, four-wheel, vehicle